Penentuan Interval Waktu Perawatan Mesin Blowing dan Mesin Filling Menggunakan Teori Reliability dan Model Age Replacement (Studi Kasus pada PT. XYZ) : - - Prasetyaningsih, Endang; Ruchiyat, Ilyas; Muhammad, Chaznin R. (TALENTA Publisher, 2020)
Engine performance will decrease when it is operated continuously so that maintenance is needed. Improper maintenance time intervals can reduce engine reliability and still causes machine damage suddenly. Therefore, maintenance time intervals must be determined precisely. This study aims to determine the engine maintenance time intervals using Reliability Theory and Age Replacement Model, then calculate the total maintenance cost. The result shows that the application of new maintenance time interval increases machine reliability.